RELATIONSHIP BETWEEN 3-MONTH INJECTION CONTRACEPTION USAGE AND BODY WEIGHT AND MENSTRUAL CYCLE - Wahidah, Nurul; Auliana, Rifa (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2025)
Background: 3-month injection contraception is an effective contraception, but it can cause menstrual cycle disorders such as amenorrhea or irregular bleeding, and is at risk of increasing body weight due to metabolic changes. The purpose of this study was to determine the relationship between the use of 3-month injection contraception and body weight and menstruation in PMB A, Bogor Regency. Method : used a quantitative method with a cross-sectional approach. The population is all 3-month injection contraception acceptors who come to PMB A totaling 74 people and all of them are used as samples. Results: showed that there was a relationship between injectable contraception and body weight with a value of p = 0.004, and there was a relationship between the type of injectable contraception and menstruation with p = 0.001. Conclusion: 3-month injectable contraception has an effect on weight gain and menstrual patterns.